Effect of Participatory Learning Model on Functional Literacy Education - Arbarini, Mintarsih; Jutmini, Sri; Joyoatmojo, Soetarno; Sutarno, Sutarno (Journal of Nonformal Education, 2018)
Participatory learning model in functional literacy education attempts to involve learners completely to contribute and to participate actively in any stages of learning activity. This research aimed to apply participatory learning model and to find out the effect of participatory learning application on functional literacy education in rural community learners. This study was a research and development by producing a participatory learning model product applied to motivate the learners in rural community learning group of Semarang Regency. The design used in developing the model product was ADDIE model. Learning model trial was carried out using experimental research with pretest-posttest control group design. The participants of research involved 2 learning group with 35 learners in experiment group and 30 learners in control group. The result of trial was analyzed using statistic t-test. The result of research showed that (1) the application of participatory learning model could grow active participation and learner independency by utilizing their self-potency and environment, 2) Participatory learning affected positively the improvement of learnersâ€™ learning motivation with the mean score difference between pretest and posttest of 12.95 experiment group higher than 4.76 control group, and the learning outcome of learners improved with the mean score difference between pretest and posttest ofÂ  0.59 experiment group)higher than 0.3 control group. The application of participatory learning model was made the literacy acceleration process by involving the learners in functional literacy education as the attempt of empowering the rural community. The implications of the participatory learning model on functional literacy education can increase the active participation of the learning community, the motivation of learning, and the competence of the learning community. The implications for this participant learning model tutor can increase the creativity and innovation in teaching the learners of functional literacy education in rural communities.